Juvenile neurogenesis makes essential contributions to adult brain structure and plays a sex-dependent role in fear memories - Cushman, Jesse D.; Maldonado, Jose; Kwon, Eunice E.; Garcia, Denise A.; Fan, Guoping; Imura, Tetsuya; Sofroniew, Michael V.; Fanselow, Michael S. (Frontiers in Behavioral Neuroscience, 2012)
Postnatal-neurogenesis (PNN) contributes neurons to olfactory bulb (OB) and dentate gyrus (DG) throughout juvenile development, but the quantitative amount, temporal dynamics and functional roles of this contribution have not been defined. By using transgenic mouse models for cell lineage tracing and conditional cell ablation, we found that juvenile neurogenesis gradually increased the total number of granule neurons by approximately 40% in OB, and by 25% in DG, between two weeks and two months of age, and that total numbers remained stable thereafter. These findings indicate that the overwhelming majority of net postnatal neuronal addition in these regions occurs during the juvenile period and that adult neurogenesis contributes primarily to replacement of granule cells in both regions. Behavioral analysis in our conditional cell ablation mouse model showed that complete loss of PNN throughout both the juvenile and adult period produced a specific set of sex-dependent cognitive changes. We observed normal hippocampus-independent delay fear conditioning, but excessive generalization of fear to a novel auditory stimulus, which is consistent with a role for PNN in psychopathology. Standard contextual fear conditioning was intact, however, pre-exposure dependent contextual fear was impaired suggesting a specific role for PNN in incidental contextual learning. Contextual discrimination between two highly similar contexts was enhanced; suggesting either enhanced contextual pattern separation or impaired temporal integration. We also observed a reduced reliance on olfactory cues, consistent with a role for OB PNN in the efficient processing of olfactory information. Thus, juvenile neurogenesis adds substantively to the total numbers of granule neurons in OB and DG during periods of critical juvenile behavioral development, including weaning, early social interactions and sexual maturation, and plays a sex-dependent role in fear memories.